1988
DOI: 10.1099/00222615-26-4-251
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the resistance to drying of staphylococcal strains

Abstract: Summary. Death rates have been determined for staphylococcal strains dried on cotton blanket material and stored at room temperature in the dark and in the light. Methicillin-resistant Staphylococcus aureus (MRSA) strains that produced a golden pigment and had a wide distribution within the hospital survived for longer periods than MRSA strains that produced little pigment and had a restricted local distribution. Death rates of methicillin-sensitive strains of S. aureus at day 7 were similar to those of the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 8 publications
2
48
0
1
Order By: Relevance
“…A major functionality of the sensor construction is the wireless remote query capability. Certain strains of S. aureus are notoriously antibiotic-resistant and responsible for over 500,000 post-surgical wound infections in the United States each year 41,42 . S. aureus has been reported to survive up to 9 weeks on standard plastic and similar dry hospital environments 42 .…”
Section: Resultsmentioning
confidence: 99%
“…A major functionality of the sensor construction is the wireless remote query capability. Certain strains of S. aureus are notoriously antibiotic-resistant and responsible for over 500,000 post-surgical wound infections in the United States each year 41,42 . S. aureus has been reported to survive up to 9 weeks on standard plastic and similar dry hospital environments 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Electron spin resonance data has shown the presence of free radicals in desiccated cells of cyanobacteria (46). Previous studies have shown that some S. aureus strains remain viable 9 weeks after desiccation (5). There was also a correlation with epidemiology, as some methicillin-resistant S. aureus strains remained viable longer than methicillin-susceptible S. aureus strains, suggesting that desiccation tolerance provides a selective advantage, leading to increased persistence (5,49).…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies have shown that some S. aureus strains remain viable 9 weeks after desiccation (5). There was also a correlation with epidemiology, as some methicillin-resistant S. aureus strains remained viable longer than methicillin-susceptible S. aureus strains, suggesting that desiccation tolerance provides a selective advantage, leading to increased persistence (5,49). We have shown that both AhpC and KatA have roles in desiccation tolerance and thus may be important for the spread of S. aureus in the hospital environment.…”
Section: Discussionmentioning
confidence: 99%
“…Survival of MRSA on non-biological surfaces varies from 1-14 days depending on the bacterial concentration in the inoculum, strain and type of surface. [16][17][18] In this series, all positive case-notes were MRSA negative when re-swabbed after 96 h implying a MRSA survival time of less than 4 days. This has implications in terms of the spread of the drug-resistant pathogens through handling of those colonised case-notes, both directly and indirectly, by healthcare workers.…”
Section: Discussionmentioning
confidence: 99%